2010
DOI: 10.1007/s11224-010-9596-8
|View full text |Cite
|
Sign up to set email alerts
|

First-principles band gap criterion for impact sensitivity of energetic crystals: a review

Abstract: In this article, we review some recent studies in predicting impact sensitivity for different classes of energetic crystals based on first-principles band gap. Based on these investigations on metal azides, a first-principles band gap criterion is founded to measure impact sensitivity for a series of energetic crystals. For energetic crystals with similar structure or with similar thermal decomposition mechanism, the smaller the band gap is, the easier the electron transfers from the valence band to the conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(122 citation statements)
references
References 59 publications
1
120
0
1
Order By: Relevance
“…Earlier, a few theoretical studies using DFT have been made on metal azides as well as organic explosives to understand the correlation between the impact sensitivity and the band gap 54 , they claimed that a small band gap and eases for electron transfer from the valence bands to the conduction bands, which leads eventually to decomposition and explosion. Fig.…”
Section: E Quasiparticle Band Structurementioning
confidence: 99%
“…Earlier, a few theoretical studies using DFT have been made on metal azides as well as organic explosives to understand the correlation between the impact sensitivity and the band gap 54 , they claimed that a small band gap and eases for electron transfer from the valence bands to the conduction bands, which leads eventually to decomposition and explosion. Fig.…”
Section: E Quasiparticle Band Structurementioning
confidence: 99%
“…6 in the crystal phase, compared with the experimental distance 2.233 Å and experimental bond angle 104. 9 . Moreover, the gas-phase BCHMX molecule is closer to the C 1 point group symmetry.…”
Section: Geometry Structuresmentioning
confidence: 99%
“…Zhu and Xiao [9] noted that there is a relationship between the band gap and impact sensitivity for different series of energetic crystals with similar structure or with similar thermal decomposition mechanism. Zhang et al [31] explained well the trend of the impact sensitivity combining the band gap computed from the crystal with the BDE of NO 2 computed from the isolated molecule.…”
Section: Impact Sensitivity Of the Bchmxmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al [31] reported that band gaps of azides and explosives, and correlated them with their sensitivity as follows: the smaller the band gap, the easiest it is to transfer an electron from the valence bands to the conduction bands and consequently an external stimuli can more easily decompose the energetic material leading to explosion. Unfortunately, the experimental band gaps are not yet reported for most of these materials, the known band gaps values of inorganic azides (between 1.61 to 4.68 eV for heavy metal azides to light metal azides) and explosives materials (2.37 eV for TATB, 3.62 eV for HMX, 3.55 eV for RDX) are from standard DFT functionals.…”
Section: Quasiparticle Band Structurementioning
confidence: 99%